Capacity Contribution Induced by Pseudo-Capacitance Adsorption Mechanism of Anode Carbonaceous Materials Applied in Potassium-ion Battery - Liu, Jiahao; Xu, Ziqiang; Wu, Mengqiang; Wang, Yuesheng; Karim, Zaghib (Frontiers in Chemistry, 2019)
The intrinsic bottleneck of graphite intercalation compound mechanism in potassium-ion batteries necessitates the exploitation of novel potassium storage strategies. Hence, utmost efforts have been made to efficiently utilize the extrinsic pseudo-capacitance, which offers facile routes by employing low-cost carbonaceous anodes to improve the performance of electrochemical kinetics, notably facilitating the rate and power characteristics for batteries. This mini-review investigates the methods to maximize the pseudo-capacitance contribution based on the size control and surface activation in recent papers. These methods employ the use of cyclic voltammetry for kinetics analysis, which allows the quantitative determination on the proportion of diffusion-dominated versus pseudo-capacitance by verifying a representative pseudo-capacitive material of single-walled carbon nanotubes. Synergistically, additional schemes such as establishing matched binder-electrolyte systems are in favor of the ultimate purpose of high-performance industrialized potassium-ion batteries.